Groundwater and urban development - Schirmer, M.; Hartog, N.; Nlend, B.; Fallas, H.; Dassargues, A.; Cetinkaya, I. D.; Jampani, Mahesh; Gogu, R. (2024)
Urban groundwater is an endangered resource as urban land use exerts enormous and very complex pressures on this resource. This session will provide an overview of urban groundwater studies in the context of urban water management, advances in hydrogeological investigation, monitoring and modelling techniques for urban areas, and highlight the challenges. Techniques for measuring pollutant concentrations, water balancing, and pollutant load estimations will be presented. To fully understand and quantify the complex urban water systems, we need to further develop our methods and combine them with new modelling approaches. In addition, it is essential to enter into an in-depth dialogue with people from urban planning, urban drainage and politics as well as the general public to raise awareness of groundwater. Only in this way will we be able to sustainably manage our water resources in and around our urban areas and incorporate them into future urban planning.